Design and Development of Swimming Pool Water pH Level Monitoring System and Automatic Selenoid Valve Control Based on the Internet of Things - Fahriza rizky maulana, Fahriza; Yusfrizal; Syari, Mili Alfhi (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
A device for monitoring the pH level of swimming pool water and an IoT-based automatic solenoid valve control has been specially designed. This system consists of several main components, including a pH sensor that continuously monitors the pH level in swimming pool water. This sensor will be connected to the Esp32 Board microcontroller which has been programmed to retrieve pH data periodically. The collected data will be sent via an internet connection to the cloud platform and can then be accessed via a mobile application to display real-time pH level messages. In addition, this system is also equipped with automatic solenoid valve control. Based on the measured pH data, the system will be able to make a decision to open or close the solenoid valve. If the pH level is outside the set limit, the system will automatically activate the solenoid valve to open the floodgates for filling water into the swimming pool, thus maintaining the pH balance automatically. In the design system for monitoring the pH level of swimming pool water and controlling this automatic solenoid valve using a pH-014 sensor which functions to detect the pH level in swimming pool water.